The development of a conservator's guidebook a manual for the preservation of manuscript music sheets of the University of the Philippines College of Music Library Filipiniana and Special Collections - Cañaveral, Ma. Lourdes Roxanne F.; Matriano, Levin G. (2014)
Well-preserved manuscript music sheets may be considered rare opportunities of observing the interdependency between tangible and intangible cultural heritage. The UP College of Music Library is in custody of manuscript music sheets in its Filipiniana and Special Collections section. Currently the library has no written policies on conservation of materials. The on-going restoration project which started in June 2011 inspired the creation of a Conservator's Guidebook specific for the type and value of collection, detailing preservative and restorative treatments appropriate for the condition of the music sheets